Comparison of Peribulbar Vs Topical Anaesthesia for Phacoemulsification - Badar- ud-din Athar Naeem , Abrar Raja, Rabia Bashir , Shahzad Iftikhar , Khawaja Naeem Akhtar , Rasheed Hussain Jaffri , Mustafa Kamal Akbar , Badar- ud-din Athar Naeem , Abrar Raja, Rabia Bashir , Shahzad Iftikhar , Khawaja Naeem Akhtar , Rasheed Hussain Jaffri , Mustafa Kamal Akbar (Journal of Rawalpindi Medical College, 2007)
Background: To compare the efficacy of topical anaesthesia with peribulbar anaesthesia in phacoemulsification. Methods: This comparative analytical study was conducted in the Department of Ophthalmology, Fauji Foundation Hospital, Rawalpindi, from February 2006 to January 2007. A total of 200 patients who underwent phacoemulsification with intraocular lens (IOL) implantation were included in this study. Patients were randomly assigned to peribulbar group (group 1, n=100) who received 4-5 ml of local anaesthetic (equal quantities of 2% xylocaine and 0.5% bupivacaine) in peribulbar region and topical group (group 2, n=100) using 0.5% proparacaine in conjunctival sac every 5 minutes for half an hour before surgery. Patients refusing informed consent, having communication problem and nystagmus were excluded from the study. All surgeries were performed by the same surgeon. Results: The difference between two groups regarding analgesia was found to be statistically insignificant. Periocular group provided significant akinesia. Conclusion: Topical anaesthesia is an effective alternative to peribulbar anaesthesia for phacoemulsification reducing the risks associated with peribulbar injection.